Implementation of UHC (Universal Health Coverage) Policy in Medan City: Implementasi Kebijakan UHC (Universal Health Coverage) Di Kota Medan - Tauhid, Azhar (LPPM UPMI, 2023)
In the current development of society, there are various kinds of communities according to their respective goals, which are more popularly known as gangs. Its members are a group of young people (teenagers) who have the same background and live in an area who are members of a two-wheeled motorized vehicle community. These teenagers' activities often involve committing criminal acts. This type of research is normative with a statutory approach. The data used is secondary data consisting of primary and secondary legal materials. Criminological studies of criminal acts committed by teenage gang members originate from internal factors (psychological) and also factors outside the self, namely economic, educational and environmental factors (micro, mini and macro). For this reason, it is recommended that parents educate and supervise their children more so that they do not join teenage gangs that commit criminal acts.